Cytotoxic effect of the VVGMCSF-Lact oncolytic virus against 3D cultures of human glioblastoma cells U-87 MG - M. A. Dymova; T. A. Shnaider; S. A. Chechetkina; G. O. Petrov; D. O. Malysheva; D. V. Drokov; A. B. Ageenko; N. S. Vasileva; V. A. Richter; E. V. Kuligina (Acta Biomedica Scientifica, 2024)
Background. One of the promising methods of treating tumors is virotherapy, which is based on direct lysis of cancer cells by a virus and a virus-mediated antitumor immune response of the body. For the recombinant vaccinia virus strain VVGMCSF-Lact, producing human GMCSF and the oncotoxic protein lactaptin, cytotoxic and antitumor effects were shown in experiments in vitro and in vivo, respectively, when using adhesive cultures of U-87 MG human glioblastoma cells. 3D cultures are a more relevant tumor model than adhesive models, as they more fully reflect the realistic scenario of cancer development, as well as the response of the tumor to anticancer therapy.The aim. To evaluate the cytotoxic effect of the oncolytic virus VV-GMCSF-Lact against 3D cultures of human glioblastoma U-87 MG.Materials and methods. The following methods were used in the work: cultivation of 3D cell cultures, cytofluorometry, microscopic analysis, virus titration, statistical analysis.Results. U-87 MG cells were transduced with a lentiviral vector carrying the GFP reporter gene. The cytotoxicity of the VV-GMCSF-Lact virus (IC50) against the studied cells was 0.024 PFU/cell. U-87 MG cells were cultured under conditions for the formation of 3D structures. Microscopic analysis showed the oncolytic effect of the virus on the cells of 3D cultures as early as 24 hours after the start of incubation. Flow cytometry showed an increase in the granularity of glioblastoma cells under the action of the virus, which indicates active replication of the virus in the cells. The virus titer was 0.44 PFU/cell.Conclusions. The recombinant VV-GMCSF-Lact virus has a cytotoxic effect on 3D human glioblastoma U-87 MG cell cultures and actively replicates in them. In the future, to test the oncolytic effect of VV-GMCSF-Lact, it is planned to use not only 3D human glioblastoma cultures, but also cerebral organelles obtained in the process of cocultivation of glioblastoma cells and induced human pluripotent cells.